The contribution of cooperatives to the productive inclusion of family farmers: a case study in Tocantins, Brazil - Neves de Sousa, Diego; Ribeiro de Jesus, Maria Eduarda (Cooperativismo & Desarrollo, 2023)
Cooperativism is a viable alternative to enhance the productive inclusion of family farmers by providing in-novation in production, distribution and commercialization in markets. The aim of this study is to analyze the perception of social mediators regarding the contribution of cooperatives to the productive inclusion of family farmers in the state of Tocantins. To this end, two data collection techniques were used: document analysis and semi-structured interviews. It is concluded that the affiliation of family farmers in a cooperative enterprise makes it possible to achieve better results than would be achieved individually, acquiring more conditions to be included productively when accessing markets, public policies and rural extension services. This is in line with the idea of productive inclusion aimed at the “production of novelties” in which the emphasis is on the socio--technical network of cooperatives, by promoting environmental sustainability actions, enhancing reciprocity ties between members and promoting the emergence of technical and organizational.
Keywords: markets; productive organization; public politics; rural development; cooperation